Resistance training as supportive measure in advanced cancer patients undergoing TKI therapy: a controlled feasibility trial - Rosenberger, Friederike; Wiskemann, Joachim; Vallet, Sonia; Haag, Georg Martin; Schembri, Emanuel; Jäger, Dirk; Grüllich, Carsten (Supportive care in cancer, 2017)
Purpose: While there is growing evidence for positive effects of progressive resistance training in curatively treated cancer patients, data on advanced cancer patients are scarce. This pilot study aimed at investigating for the first time feasibility and effects of progressive resistance training in advanced cancer patients undergoing tyrosine kinase inhibitor (TKI) therapy.MethodsPatients starting a TKI-based anti-tumor therapy were assigned to a resistance training group (RT, 12 weeks of progressive machine-based resistance training 2×/week) or a control group (CON, treatment as usual) until 10 patients had finished in each group (RT 80% males, 90% renal cell carcinoma, 65 ± 11 years, CON 80% males, 70% renal cell carcinoma, 61 ± 6 years). Primary endpoint was feasibility. Furthermore, fatigue (MFI), quality of life (QoL, EORTC QLQC30), and muscle strength were assessed. Testing occurred at baseline and after 12 weeks.Results: Training was feasible in 9 out of 10 participants and no serious adverse events occurred. It had beneficial effects on muscle strength (maximum voluntary isometric contraction of the quadriceps: RT +11 ± 9 Nm, CON −13 ± 25 Nm, p = 0.005), but not on fatigue (general fatigue score RT +0.3 ± 4.1, CON -1.5 ± 3.0, p = 0.223) or QoL (global QoL score RT −5.6 ± 16.1, CON −2.0 ± 18.2, p = 0.617).Conclusions: Progressive machine-based resistance training appears feasible in the majority of advanced cancer patients undergoing TKI therapy. However, its positive effects on muscle strength do not seem to be associated with positive effects on fatigue or quality of life. Future studies should therefore compare whether home-based training is more beneficial for patient-reported outcomes.Trial registration NCT01645150
Gesehen am 18.04.2018